Lithium ion secondary battery silicon-based negative electrode material and application thereof
By preparing the silicon-based anode material of lithium-ion secondary battery with the chemical formula of LixASiyOz, the capacity attenuation problem caused by volume strain of the silicon-based anode material in lithium-ion batteries is solved, and high energy density and excellent cycling stability are achieved.
Patent Information
- Application Number
- CN202411920254.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The volume strain formed by the silicon-based anode material in lithium-ion batteries during the lithiation process leads to the material powderization and rapid attenuation of capacity. Existing strategies such as reducing active materials, introducing additives or building hole structures will reduce the energy density of the electrode.
A silicon-based anode material of lithium ion secondary battery is adopted, with the chemical formula of LixASiyOz, where A is selected from Al, Mo, Hf, Ta, Ti, V, Zr, W, Sn and lanthanides, x:y:z=(0-5):(0.01-100):(0.01-100). The material is prepared by sintering method to form a negative electrode material with intrinsic zero strain characteristics.
The negative electrode material has high area/volume energy density, excellent cycle stability and good comprehensive lithium ion storage performance, which can maintain the stability of the material during charging and discharging and extend the cycle life of the battery.
Smart Images

Figure HDA0005207859030000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of negative electrode material metals, and in particular relates to a lithium ion secondary battery silicon-based negative electrode material and application thereof. Background Art
[0002] Lithium-ion batteries are indispensable in daily life and play a vital role in the sustainable development of society. Silicon-based anodes (including Si, SiO2, SiO and amorphous SiO x However, the Li formed during the lithiation (conversion / alloying reaction) of these materials x Si and lithium silicate have large molar volumes, which can cause huge volume strains of 180% to 300%, causing the material to pulverize and lead to rapid capacity decay.
[0003] In order to relieve the volume strain of active materials and electrodes, the following three strategies are usually adopted:
[0004] (1) Reduce the amount of silicon and silicon oxide active materials added (for example, the 4680 battery released by Tesla has a silicon content of only 10wt.%);
[0005] (2) Introducing carbon or high Young's modulus additives (usually with low specific capacity or inactive electrochemically) to buffer the expansion of oxygen-based negative electrode materials, such as compounding or doping carbon nanobelts and free carbon in silicon oxide to prepare multiphase composite ceramics SiOC that exhibit low volume strain;
[0006] (3) Constructing a pore structure at the nanoscale to buffer the expansion of single-phase silicon-based negative electrode materials.
[0007] Strategies (1) and (2) will reduce the content of active materials in the electrode, and strategy (3) will reduce the tap density of the active materials. Therefore, all three strategies will reduce the energy density of the electrode. Summary of the invention
[0008] In view of this, an object of the present invention is to provide a lithium-ion secondary battery silicon-based negative electrode material and application thereof, wherein the material has a high area / volume energy density.
[0009] The present invention provides a lithium ion secondary battery silicon-based negative electrode material having a general formula I:
[0010] Li x ASi y O z Formula I;
[0011] A is selected from Al, Mo, Hf, Ta, Ti, V, Zr, W, Sn and lanthanide elements;
[0012] x:y:z=(0~5):(0.01~100):(0.01~100).
[0013] Preferably, x is 1-2, y is 1-5, and z is 2-10.
[0014] Preferably, the negative electrode material is LiAlSiO4, LiVSiO4, LiAlSi3O8 or LiTaSi2O7.
[0015] The present invention provides a negative electrode sheet, comprising the lithium-ion secondary battery silicon-based negative electrode material described in the above technical solution.
[0016] Preferably, the negative electrode sheet comprises a current collector;
[0017] An active material layer is arranged on the surface of at least one side of the current collector, and the active material layer includes the lithium-ion secondary battery silicon-based negative electrode material described in the above technical solution.
[0018] Preferably, the active material layer further includes a binder and a conductive agent;
[0019] The mass ratio of the negative electrode material, the binder and the conductive agent is (1-8):(1-12):(0.5-5).
[0020] The present invention provides a lithium-ion battery, comprising the negative electrode sheet described in the above technical solution.
[0021] Preferably, it also includes a positive electrode sheet;
[0022] The active material in the positive electrode sheet is selected from lithium iron phosphate and / or ternary NCM material.
[0023] Preferably, it also includes a separator and an electrolyte;
[0024] The electrolyte is a LiPF6 system electrolyte.
[0025] The present invention provides a lithium ion secondary battery silicon-based negative electrode material having a general formula I: Li x ASi y O z Formula I; A is selected from Al, Mo, Hf, Ta, Ti, V, Zr, W, Sn and lanthanide elements; x:y:z=(0-5):(0.01-100):(0.01-100). The negative electrode material and the negative electrode sheet prepared therefrom have the characteristics of intrinsic zero strain and high performance (such as low operating voltage, high theoretical specific capacity and long cycle performance), which can bring excellent cycle stability and high energy density. The lithium ion secondary battery assembled with the negative electrode material has good comprehensive lithium ion storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 (a) charge and discharge curves and (b) cycle performance test results of a half-cell assembled with the LiAlSiO4 negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention provides a lithium ion secondary battery silicon-based negative electrode material having a general formula I:
[0028] Li x ASi y O z Formula I;
[0029] A is selected from Al, Mo, Hf, Ta, Ti, V, Zr, W, Sn and lanthanide elements;
[0030] x:y:z=(0~5):(0.01~100):(0.01~100).
[0031] The negative electrode material provided by the present invention has a low operating voltage and a high theoretical specific capacity, and therefore has a high area / volume energy density; the negative electrode material has an intrinsic zero strain characteristic, that is, the material itself does not expand in volume during the charge and discharge process, thereby bringing excellent cycle stability. The negative electrode material is in the form of crystal or amorphous.
[0032] In terms of molar ratio, x:y:z=(0-5):(0.01-100):(0.01-100), preferably x:y:z=(1-5):(0.1-10):(0.1-30); more preferably, x:y:z=(1-2):(1-5):(2-10).
[0033] The negative electrode material in the present invention is LiAlSiO4, LiVSiO4, LiAlSi3O8 or LiTaSi2O7.
[0034] The present invention adopts a sintering method to prepare Li x ASi y O z Silicon-based negative electrode materials for lithium-ion secondary batteries.
[0035] The silicon-based negative electrode material for lithium-ion secondary batteries described in the above technical solution of the present invention is preferably prepared according to the following method:
[0036] LiNO3, A chloride and polydimethylsiloxane with corresponding chemical formula molar coefficients are mixed in a mixed solvent, stirred, and heated to evaporate the solvent to obtain a white powder;
[0037] The white powder was ground, pressed into tablets, and sintered to obtain Li x ASi yO z .
[0038] The chlorinated A in the present invention is AlCl3, VCl3 or TaCl5.
[0039] The Li x ASi y O z It is preferably crushed and ground to obtain powdered Li x ASi y O z .
[0040] The mixed solvent in the present invention is a mixture of ethanol and water, preferably a mixture of ethanol and water in a volume ratio of 4:1; the stirring temperature is 20-30°C and the time is 25-35 minutes; the sintering temperature is 680-720°C and the sintering time is 11-13 hours; in a specific embodiment, the sintering temperature is 700°C and the time is 12 hours.
[0041] Specifically, the lithium-ion secondary battery silicon-based negative electrode material is prepared according to the following method: first, LiNO3, A chloride and polydimethylsiloxane with corresponding chemical formula molar coefficients are mixed in a mixed solvent (ethanol and water mixture), and stirred at 20-30°C for 25-35 minutes; the solution is heated to 60°C until dry to obtain a white powder; the powder is ground in a mortar and pressed into a tablet using a tablet press; the pressed tablet is sintered at 680-720°C for 11-13 hours to form Li x ASi y O z Block; the Li x ASi y O z The block is crushed and ground to obtain Li x ASi y O z powder.
[0042] The present invention provides a negative electrode sheet, comprising the lithium-ion secondary battery silicon-based negative electrode material described in the above technical solution.
[0043] The negative electrode sheet includes a current collector;
[0044] and an active material layer disposed on at least one side of the current collector, wherein the active material layer includes the lithium ion secondary battery silicon-based negative electrode material described in the above technical solution.
[0045] The current collector in the present invention is copper foil, carbon paper or carbon cloth.
[0046] The active material layer of the present invention also includes a binder and a conductive agent; the mass ratio of the negative electrode material, the binder and the conductive agent is (1-8): (1-12): (0.5-5).
[0047] In certain exemplary embodiments of the present invention, the conductive agent is commercial conductive carbon black and / or Ketjen black; and the binder is PVDF and / or SBR.
[0048] The negative electrode sheet of the present invention is preferably prepared according to the following method:
[0049] The negative electrode material, binder and conductive agent are uniformly dispersed in a solvent, coated on a current collector, and then vacuum dried to obtain a negative electrode sheet.
[0050] The coating amount is 1-20 mg / cm 2 ; Specifically, it can be 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15mg / cm 2 、16mg / cm 2 、17mg / cm 2 、18mg / cm 2 、19mg / cm 2 or 20mg / cm 2 .
[0051] The current collector in the present invention is a copper foil current collector with a thickness of 10 to 14 microns.
[0052] The present invention provides a lithium-ion battery, comprising the negative electrode sheet described in the above technical solution.
[0053] The lithium-ion battery also includes a positive electrode sheet;
[0054] The active material in the positive electrode sheet is selected from lithium iron phosphate (LiFePO4) and / or ternary NCM material.
[0055] The mass ratio of active material, conductive agent and binder in the positive electrode sheet is (1-8): (0.1-5): (0.5-5); 8:1:1. The current collector used in the positive electrode sheet is Al foil with a thickness of 8-12 microns; the coating amount is 20-30 mg / cm 2 The specific coating amount is 20mg / cm 2 , 21mg / cm 2 , 22mg / cm 2 , 23mg / cm 2 , 24mg / cm 2 , 25mg / cm 2 , 26mg / cm 2 , 27mg / cm 2 、28mg / cm 2 , 29mg / cm 2 or 30mg / cm 2 ;
[0056] The lithium-ion secondary battery assembled with the above negative electrode material has good comprehensive lithium-ion storage performance.
[0057] The lithium-ion battery further comprises a separator and an electrolyte;
[0058] The electrolyte is a LiPF6 system electrolyte.
[0059] The separator in the present invention is a polyolefin microporous membrane.
[0060] The lithium ion battery of the present invention is preferably prepared according to the following method:
[0061] The negative electrode sheet and the positive electrode sheet are separated by a separator, injected with electrolyte, and assembled to obtain a lithium-ion battery.
[0062] In order to further illustrate the present invention, a lithium ion secondary battery silicon-based negative electrode material and its application provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0063] Example 1
[0064] Preparation process of LiAlSiO4 powder:
[0065] LiAlSiO4 is prepared by sintering. First, 0.05 mol of LiNO3, 0.05 mol of AlCl3 and 0.05 mol of polydimethylsiloxane are mixed in a mixed solvent (100 ml of ethanol and 25 ml of water) and stirred at 25°C for 30 minutes. Subsequently, the solution is heated to 60°C until dry to obtain a white powder. The powder is ground in a mortar and pressed into tablets using a tablet press. Then, the pressed tablets are sintered at 700°C for 12 hours to form LiAlSiO4 blocks. Finally, the LiAlSiO4 blocks are crushed and ground to obtain LiAlSiO4 powder.
[0066] Preparation of negative electrode sheet: 80g LiAlSiO4 powder, 10g conductive carbon black and 10g PVDF powder were uniformly mixed in NMP and coated on a 12μm copper foil current collector with a coating amount of 10mg / cm 2 , and then vacuum dried to form a negative electrode membrane.
[0067] Preparation of positive electrode sheet: Conductive carbon black is used as the conductive agent, PVDF is used as the binder, and NMP is used as the solvent. After stirring evenly, the positive electrode active material LiFePO4 is added. In the mixture, the solid components include 80wt.% LiFePO4, 10wt.% binder PVDF and 10wt.% conductive carbon black. The current collector is 10μm Al foil, with a coating amount of 25mg / cm 2 .
[0068] Preparation of lithium-ion battery: using the above positive electrode and negative electrode, 1mol / L LiPF6 / (EC+DEC,
[0069] 1:1) Commercial electrolyte and polyolefin microporous membrane are assembled into soft-pack lithium-ion batteries by winding, assisted by commonly used tabs and aluminum-plastic film sealing.
[0070] The battery's charge and discharge performance, rate performance and cycle performance are as follows Figure 1 As shown, the battery has a low operating voltage (about 0.25V) (see Figure 1 (a)), excellent rate performance (capacity retention rate at 6C is higher than 50%) (see Figure 1 (a)) and excellent cycle performance: no capacity loss after 5000 cycles (see Figure 1 (b)).
[0071] Example 2
[0072] Preparation process of LiVSiO4 powder:
[0073] LiVSiO4 is prepared by sintering. First, 0.05 mol of LiNO3, 0.05 mol of VCl3 and 0.05 mol of polydimethylsiloxane are mixed in a mixed solution (100 ml of ethanol and 25 ml of water) and stirred at 25°C for 30 minutes. Subsequently, the solution is heated to 60°C until dry to obtain a white powder. The powder is ground in a mortar and pressed into tablets using a tablet press. Then, the pressed tablets are sintered at 700°C for 12 hours to form LiVSiO4 blocks. Finally, the LiVSiO4 blocks are crushed and ground to obtain LiVSiO4 powder.
[0074] Preparation of negative electrode sheet: 80g LiVSiO4 powder, 10g conductive carbon black and 10g PVDF powder were uniformly mixed in NMP and coated on a 12μm copper foil current collector with a coating amount of 10mg / cm 2 , and then vacuum dried to form a negative electrode membrane.
[0075] Preparation of positive electrode sheet: Conductive carbon black is used as the conductive agent, PVDF is used as the binder, and NMP is used as the solvent. After stirring evenly, the positive electrode active material LiFePO4 is added. In the mixture, the solid components include 80wt.% LiFePO4, 10wt.% binder PVDF and 10wt.% conductive carbon black. The current collector is 10μm Al foil, with a coating amount of 25mg / cm 2 .
[0076] Preparation of lithium-ion battery: using the above positive electrode and negative electrode, 1mol / L LiPF6 / (EC+DEC,
[0077] 1:1) Commercial electrolyte and polyolefin microporous membrane are assembled into soft-pack lithium-ion batteries by winding, assisted by commonly used tabs and aluminum-plastic film sealing.
[0078] Example 3
[0079] Preparation process of LiAlSi3O8 powder:
[0080] LiAlSi3O8 is prepared by sintering. First, 0.05 mol of LiNO3, 0.05 mol of AlCl3 and 0.15 mol of polydimethylsiloxane are mixed in a mixed solution (100 ml of ethanol and 25 ml of water) and stirred at 25°C for 30 minutes. Subsequently, the solution is heated to 60°C until dry to obtain a white powder. The powder is ground in a mortar and pressed into tablets using a tablet press. Then, the pressed tablets are sintered at 700°C for 12 hours to form LiAlSi3O8 blocks. Finally, the LiAlSi3O8 blocks are crushed and ground to obtain LiAlSi3O8 powder.
[0081] Preparation of negative electrode sheet: 80g LiAlSi3O8 powder, 10g conductive carbon black and 10g PVDF powder were uniformly mixed in NMP and coated on a 12μm copper foil current collector with a coating amount of 10mg / cm 2 , and then vacuum dried to form a negative electrode membrane.
[0082] Preparation of positive electrode sheet: Conductive carbon black is used as the conductive agent, PVDF is used as the binder, and NMP is used as the solvent. After stirring evenly, the positive electrode active material LiFePO4 is added. In the mixture, the solid components include 80wt.% LiFePO4, 10wt.% binder PVDF and 10wt.% conductive carbon black. The current collector is 10μm Al foil, with a coating amount of 25mg / cm 2 .
[0083] Preparation of lithium-ion battery: using the above positive electrode and negative electrode, 1mol / L LiPF6 / (EC+DEC,
[0084] 1:1) Commercial electrolyte and polyolefin microporous membrane are assembled into soft-pack lithium-ion batteries by winding, assisted by commonly used tabs and aluminum-plastic film sealing.
[0085] Example 4
[0086] Preparation process of LiTaSi2O7 powder:
[0087] LiTaSi2O7 was prepared by sintering. First, 0.05 mol of LiNO3, 0.05 mol of TaCl5 and 0.1 mol of polydimethylsiloxane were mixed in a mixed solution (100 ml of ethanol and 25 ml of water) and stirred at 25°C for 30 minutes. Subsequently, the solution was heated to 60°C until dry to obtain a white powder. The powder was ground in a mortar and pressed into tablets using a tablet press. Then, the pressed tablets were sintered at 700°C for 12 hours to form LiTaSi2O7 blocks. Finally, the LiTaSi2O7 blocks were crushed and ground to obtain LiTaSi2O7 powder.
[0088] Preparation of negative electrode sheet: 80g LiTaSi2O7 powder, 10g conductive carbon black and 10g PVDF powder were uniformly mixed in NMP and coated on a 12μm copper foil current collector with a coating amount of 10mg / cm 2 , and then vacuum dried to form a negative electrode membrane.
[0089] Preparation of positive electrode sheet: Conductive carbon black is used as the conductive agent, PVDF is used as the binder, and NMP is used as the solvent. After stirring evenly, the positive electrode active material LiFePO4 is added. In the mixture, the solid components include 80wt.% LiFePO4, 10wt.% binder PVDF and 10wt.% conductive carbon black. The current collector is 10μm Al foil, with a coating amount of 25mg / cm 2 .
[0090] Preparation of lithium-ion battery: using the above positive electrode and negative electrode, 1mol / L LiPF6 / (EC+DEC,
[0091] 1:1) Commercial electrolyte and polyolefin microporous membrane are assembled into soft-pack lithium-ion batteries by winding, assisted by commonly used tabs and aluminum-plastic film sealing.
[0092] From the above embodiments, it can be seen that the present invention provides a lithium-ion secondary battery silicon-based negative electrode material having a general formula I: Li x ASi y O z Formula I; A is selected from Al, Mo, Hf, Ta, Ti, V, Zr, W, Sn and lanthanide elements; x:y:z=(0-5):(0.01-100):(0.01-100). The negative electrode material and the negative electrode sheet prepared therefrom have the characteristics of intrinsic zero strain and high performance (such as low operating voltage, high theoretical specific capacity and long cycle performance), which can bring excellent cycle stability and high energy density. The lithium-ion secondary battery assembled with the negative electrode material has good comprehensive lithium-ion storage performance. Experimental results show that the battery's charge and discharge performance, rate performance and cycle performance are as follows: Figure 1 As shown, the battery has a low operating voltage (about 0.25V), excellent rate performance: the specific capacity retention rate at 6C is higher than 50%, and outstanding cycle performance: the capacity does not decay after 5000 cycles.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A lithium-ion secondary battery silicon-based negative electrode material having a general formula I: Li x ASi y O z Formula Ⅰ; A is selected from Al, Mo, Hf, Ta, Ti, V, Zr, W, Sn and lanthanide elements; x:y:z=(0~5):(0.01~100):(0.01~100).
2. The lithium-ion secondary battery silicon-based negative electrode material according to claim 1, characterized in that: x:y:z=(1~2):(1~5):(2~10).
3. The lithium-ion secondary battery silicon-based negative electrode material according to claim 1, characterized in that: The negative electrode material is LiAlSiO4, LiVSiO4, LiAlSi3O8 or LiTaSi2O7.
4. A negative electrode sheet, characterized in that: The invention comprises the lithium ion secondary battery silicon-based negative electrode material according to any one of claims 1 to 3.
5. The negative electrode sheet according to claim 4, characterized in that: The negative electrode sheet includes a current collector; An active material layer is arranged on at least one side of the current collector, wherein the active material layer comprises the lithium ion secondary battery silicon-based negative electrode material according to any one of claims 1 to 3.
6. The negative electrode sheet according to claim 4, characterized in that: The active material layer also includes a binder and a conductive agent; The mass ratio of the negative electrode material, the binder and the conductive agent is (1-8):(1-12):(0.5-5).
7. A lithium ion battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as claimed in any one of claims 4 to 6.
8. The lithium-ion battery according to claim 7, characterized in that: It also includes a positive electrode sheet; The active material in the positive electrode sheet is selected from lithium iron phosphate and / or ternary NCM material.
9. The lithium-ion battery according to claim 7, characterized in that: It also includes a diaphragm and an electrolyte; The electrolyte is a LiPF6 system electrolyte.
Citation Information
Patent Citations
Lithium ion battery cathode material and preparation method thereof
CN104810513A
Titanium lithium silicate negative electrode material of lithium ion battery and preparation method thereof
CN105152177A
Energy storage device and ionic conducting composition for use therein
CN111630688A
Negative electrode active material for lithium ion secondary battery, method for producing same, and negative electrode for lithium ion secondary battery
CN118765445A
Nonaqueous electrolyte secondary battery and manufacture thereof
JP1997293537A